-7(3x+6)=-8(4+2x)

Simple and best practice solution for -7(3x+6)=-8(4+2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3x+6)=-8(4+2x) equation:



-7(3x+6)=-8(4+2x)
We move all terms to the left:
-7(3x+6)-(-8(4+2x))=0
We add all the numbers together, and all the variables
-7(3x+6)-(-8(2x+4))=0
We multiply parentheses
-21x-(-8(2x+4))-42=0
We calculate terms in parentheses: -(-8(2x+4)), so:
-8(2x+4)
We multiply parentheses
-16x-32
Back to the equation:
-(-16x-32)
We get rid of parentheses
-21x+16x+32-42=0
We add all the numbers together, and all the variables
-5x-10=0
We move all terms containing x to the left, all other terms to the right
-5x=10
x=10/-5
x=-2

See similar equations:

| -48=7-11x=-4 | | 4x=3x=x | | 2x+500=16000 | | 4/6=k/3 | | 5d–9= | | 12g-8=9g+7 | | 10h=-5(-h+6) | | 500(2)x^=16,000 | | 2(x-4)=2+3(x+6) | | -24h=720 | | -2y-4=-y+8 | | 2x-26=4x-61=x+15 | | -6a–2a=-64 | | 5n-33=9n-81 | | 2x+1=6x+30 | | 8(3n-9)-2n=9n-7 | | 2x-26=4x-61 | | 7x-3(x+1)=x-12 | | 7=z–9 | | 8x-15=2x+6 | | –6s=–s+5 | | 13-8m-12=61 | | 1/3+2/3(3s+1)=1–s+2/3 | | 4x+5=5(x-1)+x | | 8=-2(r+-5) | | 1/3(24p=66)=3p+43 | | 13+23(3s+1)=1–s+23 | | p÷-9=12 | | 78+.4x=82 | | 14/15=42/x | | -2(1-1x)-3(1x+1)=0 | | 82+.4x=78 |

Equations solver categories